Upaya Pencegahan Demam Berdarah Dengue Dengan Menerapkan Perilaku Hidup Bersih Dan Sehat Di SMPN 191 Jakarta Barat - Veza Azteria; Adiella Glenandra; Muhammad Rayhan; Presila Tamara Zhafira; Yona Karisma; Aurora Putri Wulandari (Pelita Masyarakat, 2025)
Aedes Aegypti is the cause of Dengue Hemorrhagic Fever (DHF), which is transmitted by its bite. Schools are one of the locations that cause the transmission and spread of dengue fever due to the cleanliness of the school environment and school sanitation, which is still classified as not yet clean. This community service aims to educate students on preventing the spread of dengue hemorrhagic fever by implementing clean and healthy living behavior in the school environment. Community service methods include socialization, pre-test, and post-test, student education using lecture methods, and discussions with students. The community service results stated that there was an increase in the knowledge of students at SMPN 191 West Jakarta in understanding the implementation of PHBS in the school environment as an initial effort to prevent the spread of dengue fever in the school environment. In this activity, information was obtained that 79.95% of students' knowledge had increased regarding the application of PHBS, especially in washing hands using soap. However, several points that were not optimal were consuming healthy food in the school canteen area.